Experimental study to characterize water contaminated by lunar dust - Freer, Rieke; Pesch, Victoria; Zabel, Paul (Frontiers in Space Technologies, 2024)
The establishment of a permanent lunar base is the goal of several space missions, such as NASA's Artemis program. The feasibility of a lunar base is highly dependent on the supply of clean water, which can be recycled within the life support system or extracted in-situ on the Moon. Contamination of the water by lunar dust is an unavoidable problem due to the fact that lunar dust covers the entire surface and has adhesive properties as well as a very fine particle size.It is therefore important to study and characterise water contaminated by lunar dust in order to develop a safe water supply system. We combined existing studies on the dissolution behaviour of lunar regolith in aqueous solutions and performed dissolution experiments ourselves. We conducted dissolution experiments using the Lunar Highland Dust simulant from Exolith Lab (Orlando, USA), which resembles the Apollo 16 regolith and thus the terrain of the suspected Artemis landing sites. Our dissolution experiments investigate the effects of the dust to solution ratio, the aqueous solution used (ultrapure water and 5.5 buffer), the short exposure time (2 min up to 72 h), the dissolved oxygen in the solutions and the particle size of the simulant. As a result, this study provides a characterisation of lunar dust contaminated water and compares the results with the World Health Organization (WHO) and NASA requirements for drinking water. For all test batches, the lunar dust contaminated water exceeds the requirements for pH, turbidity and Al concentration.